Extrapolated skin dose assessment with optically stimulated luminescent dosimeters. (27th July 2016) - Butson, Martin; Chen, Tom; Alzaidi, Samara; Pope, Dane; Butson, Ethan; Gorjiara, Tina; Poder, Joel; Cho, Gwi; Gill, Simran; Morales, Johnny; Haque, Mamoon; Whitaker, May; et al.
Abstract: A novel method is described for the measurement and calculation of surface and skin dose during megavoltage x-ray therapy utilising an extrapolation technique with optically stimulated Dosimeters. The technique utilises three configurations of an Optically Stimulated Luminescence (OSL) detector which provide different effective depth of measurement points. This allows the user to assess percentage build up dose at effective depths of 0.35, 0.55 and 0.85 mm. Performing an extrapolation technique, percentage dose at other effective depths such as the surface (0 mm) or the Basal Cell layer (70 μ m) depth can be estimated. Results have shown that extrapolated percentage dose of Dmax at a depth of 0.048 mm are 17.3% ± 2.3%, 28.2% ± 3.5% and 37.8% ± 3.8% for field sizes of 10 cm × 10 cm, 20 cm × 20 cm and 30 cm × 30 cm respectively. Comparative results measured with the Attix chamber which has an estimated effective depth of 0.048 mm were 16.5%, 28% and 36.8% respectively, thus showing close agreement (within 1%) with the extrapolation technique. The OSL extrapolation technique will allow users of OSL detectors to accurately assess surface and skin dose using this technique.